THE IMPACT OF FISCAL POLICY AND LEGAL REGULATIONS ON THE ISLAMIC FINANCE INDUSTRY - Sapta Nur Fallah (Adisam Publisher, 2025)
This study aims to analyse the impact of Islamic fiscal policy and legal regulation on the growth and stability of the Islamic finance industry in Indonesia. Through a desk study approach, this research finds that fiscal policies such as tax incentives, zakat management, and sukuk issuance play an important role in improving liquidity and expanding access to Islamic financing. On the other hand, comprehensive legal regulations from the government and relevant authorities, including OJK and Bank Indonesia, have created a more conducive environment for product innovation, strengthened governance, and increased public confidence in Islamic financial institutions. However, the dualism of the national and sharia legal systems, limited human resources, and regulatory harmonisation challenges are still obstacles in optimising the growth of this industry. This study recommends strengthening regulatory integration, improving sharia literacy, and cross-institutional collaboration as the main strategies to accelerate the development of a sustainable and competitive Islamic finance industry at the national and global levels.